KESADARAN POLITIK BERKETUHANAN SEBAGAI DASAR UNTUK MEWUJUDKAN KESEJAHTERAAN RAKYAT INDONESIA - Putra, Andri Azis; Kuswanjono, Arqom; Munir, Misnar (Universitas Islam Negeri Imam Bonjol Padang, 2020)
Welfare is one of the significant problems in human life. All aspects of human life politically will always be related, both as elements and indicators of welfare conditions. Consequently, the state is an organization and authority that can provide a measure and effectively regulate all efforts in the realization of people's welfare. However, practically